Evaluasi Ketersediaan dan Penempatan Alat Pemadam Api Ringan di Tenant Gedung Terminal Domestik - Dzaky Novan Syahputra; Rini Sadiatmi; Ahmad Faridan Juniwan (QISTINA: Jurnal Multidisiplin Indonesia, 2025)
Fire safety in airport environments is a crucial aspect that must be properly addressed, particularly regarding the provision of Fire Extinguishers (APAR). This study aims to evaluate the availability and placement of APAR units in tenant areas of the Domestic Terminal Building at Jenderal Ahmad Yani International Airport. A descriptive qualitative approach was used, with data collected through observation, interviews, and documentation. The findings reveal that several tenants do not yet have independently provided APARs, and some existing units are not positioned according to safety standards—being hard to see, difficult to access, or lacking proper signage. In addition, employee understanding of APAR use remains limited. These findings highlight the importance of compliance with fire safety regulations and the need for regular education and supervision. Proper placement and accessibility of APARs are essential to improve preparedness in the event of a fire emergency.